The Influence of Taste, Word of Mouth and Consumer Satisfaction on Panada Dapur Mayank South Jakarta Purchasing Decisions - Eunike Threisa Lintong; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the influence of Taste, Word of Mouth and Consumer Satisfaction on the Purchasing Decision of Panada Dapur MayankSouth Jakarta. The population in this study used Anderson sampling technique where the population taken amounted to 96 people with a significance level of 95% and a standard deviation of 25%. This study used primary data with a data collection method through questionnaires distributed to 96 respondents. Data analysis techniques using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) program version 26.0. The results showed that Taste had a positive and significant effect on Purchasing Decisions with a path coefficient value of 0.553 and a significant t of 0.000. Word Of Mouth has a positive and significant effect on Purchasing Decisions with a path coefficient value of 0.248 and a significant t of 0.001. Consumer Satisfaction has a positive and significant effect on Purchasing Decisions with a path coefficient value of 0.508 and a significant t of 0.000.